The Background of a Patient Undergoing Long-Term Periodontal Disease Maintenance Using Step for Coding and Theorization: A Case Report - Kosuke Muraoka; Masaki Morishita; Taiji Nakamura; Keisuke Nakashima; Shuji Awano (Hindawi Limited, 2024)
Periodontal maintenance is crucial for long-term periodontal stability, but some patients do not undertake maintenance following their initial treatment. To date, the motivations, backgrounds, and concerns of patients who underwent maintenance have not been researched. Therefore, we analyzed the subject's intentions and the behavior of the patient affected by periodontal maintenance using Step for Coding and Theorization (SCAT). The subject was a 50-year-old woman diagnosed with periodontitis. Periodontal therapy included oral hygiene instruction, scaling, root planing, and periodontal surgery. She has been continuing maintenance for 21 years. An interview was conducted on a one-to-one basis, between the patient and the surgeon, using a semistructured interview. The contents of the interview included her reasons for visiting the university hospital and her reasons for continuing maintenance. For the qualitative analysis using SCAT, the vocabulary obtained from the interview was filled out in a SCAT form. We determined that the relationship between the dental personnel and the patient was good, and we could convey the importance of maintenance to the patient. Appropriate periodontal treatment and the maintenance of a good relationship with the dental health oral care provider are key factors in improving the rate of maintenance visits and ensuring long-term periodontal stability.